RSSA feasibility study : final report : Caricom Secretariat (KPMG Peat Marwick [Port of Spain]TT, 1994)
Seeks to improve regional communications; determine the appropriateness and the financial, economic and institutional feasibility of a Regional space Segment Agency (RSSA); and prepare, if an RSSA is deemed to be feasible, a time-bound implementation plan for its establishment.
DC